CAN SEAWEED FARMING IN THE TROPICS CONTRIBUTE TO CLIMATE CHANGE THROUGH EMISSION OF SHORT-LIVED HALOCARBONS? - Phang, Siew-Moi; Keng, Fiona Seh-Lin; Mithoo Singh, Paramjeet-Kaur; Lim, Yong-Kian; Abd Rahman, Noorsaadah; Leedham, Emma C.; Robinson, Andrew D.; Harris, Neil R.P.; Pyle, John A.; Sturges, William T. (Malaysian Journal of Science, 2015)
Volatile halocarbons form a major source of halogen radicals in the atmosphere, which are involved in the catalytic destruction of ozone. Studies show that marine algae release halocarbons, with 70% of global bromoform produced by marine algae (Carpenter et al., 2000). The role of halocarbons in algae is linked to their use as defense against epiphytes and grazing as well as scavengers of strong oxidants (Nightingale et al., 1995). Halocarbon release rates are higher for tropical algae than temperate species (Abrahamsson et al., 1995). The Maritime Continent is a major contributor to emissions of short-lived halocarbons and their transport to the stratosphere due to deep convection. The Coral Triangle situated in the Maritime Continent, is a centre for seaweed farming. The following discusses the potential impact of tropical seaweed emissions of halogenated compounds to climate change. ABSTRAK Halokarbon mudah meruap adalah sumber utama radikal halojen dalam atmosfera, yang terlibat dalam pemusnahan lapisan ozon. Kajian menunjukkan bahawa alga melepaskan halokarbon, dan 70% bromoform dihasilkan oleh alga marin (Carpenter et al., 2000). Peranan halokarbon dalam alga berfungsi sebagai pertahanan terhadap epifit dan ‘oxidant scavengers’ yang kuat (Nightingale et al., 1995). Kadar pengeluaran halokarbon adalah lebih tinggi untuk alga tropika daripada spesies sederhana (Abrahamsson et al., 1995). Benua Maritim adalah pengeluar utama bagi halokarbon jangka hayat pendek dan pengangkutannya ke stratosfera disebabkan perolakan dalam Segitiga Terumbu Karang yang diletak dalam Benua Maritim, adalah pusat pengkulturan rumpai laut. Kertas ini membincangkan impak daripada pengeluaran halokarbon daripada rumpai laut terhadap perubahan iklim. Keywords: Volatile halocarbons, Marine algae, Seaweed farms, Maritime Continent, Climate change